Problem gambling and economic abuse against women: an adaptive grounded theory analysis. (4th May 2022) - Hing, Nerilee; Nuske, Elaine; Breen, Helen; O'Mullan, Catherine; Mainey, Lydia; Thomas, Anna
Abstract: Problem gambling provides a strong motivation for perpetrating economic abuse. This study explores the interaction between problem gambling and economic abuse, and how this economic abuse is reinforced by other forms of intimate partner violence (IPV) and underpinned by gendered drivers of violence against women. Interviews were conducted with 18 women with lived experience of economic abuse perpetrated by a male partner with a gambling problem and analyzed using adaptive grounded theory. The women reported that their partner subjected them to numerous forms of economic exploitation (e.g. fraudulent use of her credit card) and economic control (e.g. preventing her from accessing money) to fund his gambling. Patterns of psychological and physical abuse reinforced this economic abuse. Gendered drivers of this violence underpinned this behavior including their partner's perceived entitlement to subordinate, control, and manipulate them. The resulting financial stress undermined the women's capacity to leave the relationship, extending their victimization and deprivation. This integrated exploration highlights that problem gambling and gendered drivers of violence interact to create a context where economic abuse and other forms of violence are perpetrated to obtain money for gambling. Interventions by gambling operators, financial institutions, and support services are needed to reduce gambling-related economic abuse.